Single-cell RNA datasets and bulk RNA datasets analysis demonstrated C1Q+ tumor-associated macrophage as a major and antitumor immune cell population in osteosarcoma - Tu, Jihao; Wang, Duo; Zheng, XiaoTian; Liu, Bin (Frontiers in Immunology, 2023)
Background: Osteosarcoma is the most frequent primary bone tumor with a poor prognosis. Immune infiltration proved to have a strong impact on prognosis. We analyzed single-cell dataset and bulk datasets to confirm the main immune cell populations and their properties in osteosarcoma. Methods: The examples in bulk datasets GSE21257 and GSE32981 from the Gene Expression Omnibus database were divided into two immune infiltration level groups, and 34 differentially expressed genes were spotted. Then we located these genes among 9 major cell clusters and their sub-clusters identified from 99668 individual cells in single-cell dataset GSE152048 including 11 osteosarcoma patients. Especially, the markers of all kinds of myeloid cells identified in single-cell dataset GSE152048 were set to gene ontology enrichment. We clustered the osteosarcoma samples in the TARGET-OS from the Therapeutically Applicable Research to Generate Effective Treatments dataset into two groups by complete component 1q positive macrophage markers and compared their survival. Results: Compared with the low-immune infiltrated group, the high-immune infiltrated group showed a better prognosis. Almost all the 34 differentially expressed genes expressed higher or exclusively among myeloid cells. A group of complete component 1q positive macrophages was identified from the myeloid cells. In bulk dataset TARGET-OS, these markers and the infiltration of complete component 1q positive macrophages related to longer survival. Conclusions: complete component 1q positive tumor associated macrophages were the major immune cell population in osteosarcoma, which contributed to a better prognosis.